KONTEKS SOSIAL PADA PODCAST DENNY SUMARGO DAN INARA RUSLI SERTA RELEVANSI TERHADAP MATERI DISKUSI DI MA MODEL ZAINUL HASAN GENGGONG - Dwi Ainur Rosyidah; Endah Tri Wisudaningsih; Magfirotul Hamdiah ((JIBS) JURNAL ILMIAH BAHASA DAN SASTRA, 2026)
This study aims to describe the social context in the podcasts by Denny Sumargo and Inara Rusli, as well as the social context in Indonesian language learning using discussion materials at the Zainul Hasan Genggong Model Islamic High School, based on Dell Hymes’ SPEAKING model. The research method employed is descriptive qualitative. Data collection was carried out using note-taking, observation, interviews, and documentation to strengthen the data obtained. The data analysis technique used was the Miles and Huberman model, which includes data condensation, data presentation, and drawing conclusions. The validity of the findings in this study was assessed using the techniques of credibility, transferability, dependability, and confirmability. The results of the analysis were also discussed with the supervisor as a form of interpretative validation of the pragmatico-semantic meanings found. The research results indicate that the social context in the podcasts featuring Denny Sumargo and Inara Rusli, as well as Indonesian language learning using discussion materials at MA Model Zainul Hasan Genggong, fulfil the elements of Dell Hymes’ SPEAKING framework, which include setting and scene, participants, ends, act sequence, key, instrumentalities, norms, and genre. There are similarities in dialogic communication patterns, active participant involvement, and the application of communication norms in both speech events, despite differences in the level of linguistic formality and communicative purpose.